2014
DOI: 10.1038/bjc.2014.593
|View full text |Cite
|
Sign up to set email alerts
|

miR-1228 promotes the proliferation and metastasis of hepatoma cells through a p53 forward feedback loop

Abstract: Background:The effective mechanisms of microRNAs (miRNAs) functions as oncogenes or tumour suppressors in human hepatocellular carcinoma (HCC) are still obscure. Here, we investigated the function and expression of miR-1228 in HCC.Methods:The role of miR-1228 in HCC was determined by colony formation, transwell, and nude mice xenograft experiments. miR-1228 target gene were identified by EGFP reporter assays, real-time PCR, and western blot analysis. Dual-luciferase reporter assay and real-time PCR analysis ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 44 publications
3
37
0
Order By: Relevance
“…However, in different cell systems, p53 mRNA levels have been shown to be regulated by adjusting the rate of transcription (histone deacetylases (HDAC9, [59]), by modulation of mRNA stability (i.e. via miRNA-1228 [57]) or by hybridization of antisense transcript Wrap53 [29]. Also, in the p53 promoter, response elements of several transcription factors [43], [e.g., cAMP-responsive element-binding protein (CREB [38])], have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…However, in different cell systems, p53 mRNA levels have been shown to be regulated by adjusting the rate of transcription (histone deacetylases (HDAC9, [59]), by modulation of mRNA stability (i.e. via miRNA-1228 [57]) or by hybridization of antisense transcript Wrap53 [29]. Also, in the p53 promoter, response elements of several transcription factors [43], [e.g., cAMP-responsive element-binding protein (CREB [38])], have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the over-expression of miR-1228 can negatively regulate p53 expression, and the down-regulation of p53, in turn, increases miR-1228 expression. This positive-feedback loop contributes to the progression of HCC[110]. Studies also showed that oncogenic pathways are regulated by noncoding-RNAs.…”
Section: Regulatory Mechanism Of Glucose Metabolic Reprogrammingmentioning
confidence: 99%
“…Contrary to bening lesions, malignant tumours display higher S-phase, G 2 /M fraction and abnormal DNA ploidy [5]. Furthermore, the sum of both S-phase and G 2 /M fractions and of the S + G 2 /M/G 0 /G 1 , that is also known as proliferation index, provide additional information [10]. In gliomas, Coons et al found three groups of astrocytoma patients with significantly different survival patterns, based on S-phase fraction ranges of <3%, 3-5.9%, and greater or equal to 6%, whereas a weaker association between ploidy and survival was reported [11].…”
Section: Discussionmentioning
confidence: 99%